2000
DOI: 10.1046/j.1523-1755.2000.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the prevalence of arteriovenous fistulas in hemodialysis patients in the HEMO Study

Abstract: Factors associated with the prevalence of arteriovenous fistulasVascular access procedures and their subsequent comin hemodialysis patients in the HEMO Study. plications represent major causes of morbidity, hospital-Background. Arteriovenous (AV) fistulas are the vascular ization, and cost for chronic hemodialysis patients [1-4]. access of choice for hemodialysis patients, but only about 20% Over 20% of hospitalizations in hemodialysis patients of hemodialysis patients in the United States dialyze with fistuin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
3
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 1 publication
5
62
3
1
Order By: Relevance
“…1 Female gender has been repeatedly shown to be a strong predictor of AVG use. 1,20,29,30 Similarly, a number of studies have demonstrated that AVF are used less commonly in African-Americans. 16,29 Increased age 20,29 and presence of diabetes 20 have also been associated with decreased prevalence of fistula use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Female gender has been repeatedly shown to be a strong predictor of AVG use. 1,20,29,30 Similarly, a number of studies have demonstrated that AVF are used less commonly in African-Americans. 16,29 Increased age 20,29 and presence of diabetes 20 have also been associated with decreased prevalence of fistula use.…”
Section: Discussionmentioning
confidence: 99%
“…1,20,29,30 Similarly, a number of studies have demonstrated that AVF are used less commonly in African-Americans. 16,29 Increased age 20,29 and presence of diabetes 20 have also been associated with decreased prevalence of fistula use. Furthermore, age, 13,19,31 diabetes, 1,10,32 female gender, 1,33 and history of previous failed dialysis access 7,28,34 have been shown to predict access failure.…”
Section: Discussionmentioning
confidence: 99%
“…In the Hemodialysis (HEMO) Study, female sex was identified as a significant predictor of graft rather than AVF use, 3 but there is little specific evidence for AVF patency differences between sexes. Women may present with smaller-caliber arteries and may therefore be expected to have lower AVF patency rates than men.…”
Section: Patient Factorsmentioning
confidence: 99%
“…However, when an uncomplicated functional fistula can be quickly achieved to provide prescribed dialysis, then, indeed, it is an ideal access. The finding that AVF rates differ between countries, regions, and even individual centers [33,34] demonstrates that improvement in functional fistula rates is possible. As individual patient characteristics, including age, sex, and comorbidity, as well as vessel size and quality, may influence the chance of fistula failure, preoperative screening and planning may improve the primary maturation rates [35].…”
Section: Evidencementioning
confidence: 99%